Case Report: Migraine-Induced Dystonia of the Lower Extremities - Jiang, Ting; Xie, Yinyin; Maimaiti, Buajieerguli; Cheng, Yu; Li, Zhaoran; Meng, Hongmei (Frontiers in Neurology, 2022)
Migraine is a highly prevalent neurological disorder characterized by recurrent, unilateral, or bilateral throbbing severe headaches. Currently, there are extremely rare cases of migraine-induced dystonia. A 52-year-old woman was admitted for intractable migraine for about five days and walking difficulties for one day. The symptom of an inability to walk appeared on the fourth day of the headache attack lasting for one day and resolved on its own as the headache subsided. The same symptoms appeared once six years ago. Neurological examination, brain Magnetic resonance imaging (MRI), laboratory tests of blood and cerebrospinal fluid (CSF) were normal. The contrast transcranial doppler echocardiography (cTCD) revealed a latent and massive right-to-left shunt (RLS) after the release of the Valsalva maneuver. The patient was diagnosed with migraine-induced dystonia of the lower limbs. Oral ibuprofen and flunarizine and avoidance of increased chest pressure maneuvers were used for treatment and prevention. During the 6-month follow-up, the patient was free of headaches and walking difficulties. Our study reported a rare case of migraine-induced dystonia of the lower extremities.